Density distributions, form factors and reaction cross sections for exotic 11Be and 15C nuclei - Abdullah, Ahmed N. (Iraqi Journal of Physics, 2019)
The ground state proton, neutron and matter densities of exotic 11Be and 15C nuclei are studied by means of the TFSM and BCM. In TFSM, the calculations are based on using different model spaces for the core and the valence (halo) neutron. Besides single particle harmonic oscillator wave functions are employed with two different size parameters Bc and Bv. In BCM, the halo nucleus is considered as a composite projectile consisting of core and valence clusters bounded in a state of relative motion. The internal densities of the clusters are described by single particle Gaussian wave functions. Elastic electron scattering proton form factors for these exotic nuclei are analyzed via the plane wave born approximation (PWBA). As the calculations in the BCM do not distinguish between protons and neutrons, the calculations of the proton form factors are restricted only by the TFSM. The reaction cross sections for these exotic nuclei are studied by means of the Glauber model with an optical limit approximation using the ground state densities of the projectile and target, where these densities are described by single Gaussian functions. The calculated reaction cross sections at high energy are in agreement with the experimental data.